Molecular characterization and expression of sensory neuron membrane proteins in the parasitoid Microplitis mediator (Hymenoptera: Braconidae). (14th March 2019) - Shan, Shuang; Wang, Shan‐Ning; Song, Xuan; Khashaveh, Adel; Lu, Zi‐Yun; Dhiloo, Khalid Hussain; Li, Rui‐Jun; Gao, Xi‐Wu; Zhang, Yong‐Jun
Abstract: Sensory neuron membrane proteins (SNMPs), homologs of the human fatty acid transport protein CD36 family, are observed to play a significant role in chemoreception, especially in detecting sex pheromone in Drosophila and some lepidopteran species. In the current study, two full‐length SNMP transcripts, MmedSNMP1 and MmedSNMP2, were identified in the parasitoid Microplitis mediator (Hymenoptera: Braconidae). Quantitative real‐time polymerase chain reaction analysis showed that the expression of MmedSNMP1 was significantly higher in antennae than in other tissues of both sexes. In addition, the MmedSNMP1 transcript was increased dramatically in newly emerged adults and there were no significant differences between adults with or without mating and parasitic experiences. However, compared with MmedSNMP1, the expression of MmedSNMP2 was widely found in various tissues, significantly increased at half‐pigmented pupae stage and remained at a relatively constant level during the following developmental stages. It was found that MmedSNMP1 contained eight exons and seven introns, which was highly conserved compared with other insect species. In situ hybridization assay demonstrated that MmedSNMP1 transcript was distributed widely in antennal flagella. Among selected chemosensory genes (odorant binding protein, odorant receptor, and ionotropic receptor genes), MmedSNMP1 only partially overlapped with MmedORco in olfactory sensory neurons of antennae. Subsequent immunolocalization results further indicated that MmedSNMP1 was mainly expressed in sensilla placodea of antennae and possibly involved in perceiving plant volatiles and sex pheromones. These findings lay a foundation for further investigating the roles of SNMPs in the chemosensation of parasitoids.